EFEKTIVITAS PENGGUNAAN INTERVENSI MICROWAVE DIATHERMY, TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION DAN THERABAND EXERCISE PADA KASUS OSTEOARTHRITIS KNEE SINISTRA - Siti Saarah; Irine Dwitasari Wulandari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Osteoarthritis (OA) is a degenerative joint disease involving cartilage, joints, ligaments, and bones, leading to pain and joint stiffness. Physiotherapy problems in left knee Osteoarthritis (Osteoarthritis Knee Sinistra) include tenderness and movement pain, muscle spasm, limited range of motion, decreased muscle strength, and reduced functional activity. This study aimed to determine the effectiveness of physiotherapy management in a case of left knee osteoarthritis using Microwave Diathermy, Transcutaneous Electrical Nerve Stimulation (TENS), and Theraband Exercise. The study was conducted at Bendan Regional Public Hospital, Pekalongan City, using a descriptive-analytic research design. The subject was a patient with left knee osteoarthritis treated with the mentioned modalities. Data collection and analysis were carried out through autoanamnesis interviews and physical examinations. The instruments used included the VAS, palpation, goniometer, Medical Research Council (MRC), and WOMAC. The results after four therapy sessions were as follows: (1) decreased tenderness pain from T1=1 to T4=0 and movement pain from T1=4 to T4=0; (2) reduced quadriceps muscle spasm from T1=1 to T4=0; (3) improved range of motion from T1=Sa 5°-5°-105° to T4=Sa 0°-0°-120° and T1=Sp 0°-0°-105° to T4=Sp 0°-0°-125°; (4) increased muscle strength of knee flexors from T1=4 to T4=5 and extensors from T1=4 to T4=5; (5) improved functional activity from T1=30 (moderate) to T4=2 (mild). In conclusion, Microwave Diathermy, TENS, and Theraband Exercise effectively reduce pain and muscle spasm, while improving joint range of motion, muscle strength, and functional activity.